The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/pr6120252
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Criteria Decision-Making (MCDM) Approach Using Hybrid SCOR Metrics, AHP, and TOPSIS for Supplier Evaluation and Selection in the Gas and Oil Industry

Abstract: Suppliers are extremely important in business operations. The supplier ensures the supply of materials, raw materials, commodities, etc. in sufficient quantity, quality, stability, and accuracy to meet the requirements of production and business with low costs and on-time deliveries. Therefore, selecting and managing good suppliers is a prerequisite for organizing the production of quality products as desired, according to the schedule, and with reasonable prices and competitiveness in the market. It is also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 18 publications
0
46
0
14
Order By: Relevance
“…The Charnes-Cooper-Rhodes (CCR) model is a basic DEA model [22]. The definition of the CCR model is as follows:…”
Section: Dea Modelmentioning
confidence: 99%
“…The Charnes-Cooper-Rhodes (CCR) model is a basic DEA model [22]. The definition of the CCR model is as follows:…”
Section: Dea Modelmentioning
confidence: 99%
“…Asset management efficiency Financial situation of suppliers [10,11,14,16,17,20] Payment term allowed Revenue over a year Inventory amount of suppliers Supply chain operation reference was proposed in 1996 [8,9] by Theodore Pittiglio, Robert Rabin, Robert Todd, and Michael McGrath [10]. Specifically, the SCOR model describes business activities related to meeting customer needs, including planning, sourcing, execution, delivery, and return.…”
Section: Maintenance Cost Transportation Costsmentioning
confidence: 99%
“…This model allows companies to conduct comprehensive analysis based on practically all aspects of their supply chain by providing a complete set of process, performance, and real-life metrics best practices in the industry [10]. The performance attributes of SCOR data are shown below [11]. The SCOR's process includes: definition of process components, input-output, process performance data, selected best supplier [8,[12][13][14][15].…”
Section: Maintenance Cost Transportation Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of different (fuzzy) multi-objective decision-making methods, or problems with an integration of fuzzy weights to their algorithms, clearly confirmed that the fuzzy set theory and its corresponding developments have enough capability to properly deal with the subjectivity of experts' opinions, and it is also strongly necessary. [23][24][25] In order to formulate the aggregation procedure about the opinions obtained by exports, a mathematical programming can make valid outputs, which are feasible and optimum. 26,27 In this accordance, the main aim of this study is to introduce a heuristic approach based on a mathematical programming as well as an extension to fuzzy set theory.…”
Section: Introductionmentioning
confidence: 99%